1989
DOI: 10.1088/0264-9381/6/4/007
|View full text |Cite
|
Sign up to set email alerts
|

A realistic stellar model based on an ansatz of Duorah and Ray

Abstract: It is shown that the analytical stellar model of Duorah and Ray (1987) does not satisfy Einstein's field equations. All possible solutions derivable from the generalised density distribution are exhibited; these include a solution due to Durgapal and Bannerji. The correct solution following from the ansatz of Duorah and Ray is given. The equation of state for the model is obtained in terms of elementary functions, and the solution is shown to be both regular and physically realistic for a range of masses and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
220
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(230 citation statements)
references
References 13 publications
7
220
0
1
Order By: Relevance
“…The spacetime geometry of Finch and Skea (1989), originally developed by Duorah and Ray (1987), has got much attention in the modelling of relativistic compact stars as the solution is well-behaved and satisfies all criteria of physical acceptability (Delgaty and Lake (1998)). The Finch-Skea isotropic stellar model has subsequently been generalized by many investigators to study a large variety of stellar bodies by incorporating electro-magnetic field and anisotropic pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The spacetime geometry of Finch and Skea (1989), originally developed by Duorah and Ray (1987), has got much attention in the modelling of relativistic compact stars as the solution is well-behaved and satisfies all criteria of physical acceptability (Delgaty and Lake (1998)). The Finch-Skea isotropic stellar model has subsequently been generalized by many investigators to study a large variety of stellar bodies by incorporating electro-magnetic field and anisotropic pressure.…”
Section: Introductionmentioning
confidence: 99%
“…1 Introduction Finch and Skea (1989), making use of Duorah and Ray (1987) ansatz for the metric potential g rr corresponding to a static spherically symmetric perfect fluid spacetime, developed a stellar model which was later shown to comply with all the physical requirements of a realistic star by Delgaty and Lake (1998). Consequently, the Finch-Skea model has been explored by many investigators in different astrophysical contexts, particularly for the studies of cold compact stellar objects (see for example, Hansraj and Maharaj (2006); Tikekar and Jotania (2009) ;Banerjee et al (2013)).…”
mentioning
confidence: 99%
“…Consequently, the Finch-Skea model has been explored by many investigators in different astrophysical contexts, particularly for the studies of cold compact stellar objects (see for example, Hansraj and Maharaj (2006); Tikekar and Jotania (2009) ;Banerjee et al (2013)). One noticeable feature of the Finch and Skea (1989) model is that it assumes isotropy in pressure. However, theoretical investigations of Ruderman (1972) and Canuto (1974), amongst others have shown that anisotropy might develop in the high density regime of compact stellar objects.…”
mentioning
confidence: 99%
See 2 more Smart Citations